PENGARUH ORGANISASI SEKOLAH DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII MTs. DARUL ULUM KOTABARU TP. 2016/2017 (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
ABSTRACTThis research is madeto find out the influence of school organization and learningstyle toward mathematic learning achievement. As follows: 1) To find out theinfluence between student activity in school organization toward mathematiclearning achievement, 2) To find out the influence between learning style towardmathematic learning achievement, 3) To find out the influence between studentactivity in organization and learning styletoward mathematic learningachievement.The research is quantitative research which used descriptive method. The purposeof this research is giving description about the influence of student activity in schoolorganization and learning style student toward mathematic learning achievementof eight grade student MTs. Darul Ulum Kotabaru academic year 2016/2017.The result of this research: 1) there is significant influence between studentactivityin organization at school toward learning achievement, 2) there issignificant influence between student learning style toward learning achievement,and 3) there is significant influence between students activity in organization atschool toward student learning style.Keywords: School Organization, Learning Style and Learning Achievement